Fleksibilitas Kurikulum MBKM dalam Menanggapi Dinamika Proyek Kemanusiaan - Wianto, Elizabeth; Tjandra, Miki; Clara, Beverly; Fiona, Sharren (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Changes in the higher education curriculum with the concept of Independent Learning are responded to through various teaching-learning patterns. This situation needs to be addressed with an understanding on the part of educational institutions that the face-to-face learning model in the classroom is not the only best way. Students need to gain learning experience in the real world so that the development of their character, attitudes, and skills can be honed properly. Unfortunately, this often becomes more complex, when project assignments given are completely different from student competencies. In this case, many lecturers would prefer conventional learning with a regular curriculum which seems more responsible. For this reason, it is necessary to be flexible, especially with supervisors and university partners to optimize students' willingness to go into society as an opportunity for both students and the community to serve.